Regulation of Corynebacterium glutamicum Heat Shock Response by the Extracytoplasmic-Function Sigma Factor SigH and Transcriptional Regulators HspR and HrcA - Ehira, Shigeki (American Society for Microbiology (ASM), 2009)
Heat shock response in Corynebacterium glutamicum was characterized by whole-genome expression analysis using a DNA microarray. It was indicated that heat shock response of C. glutamicum included not only upregulation of heat shock protein (HSP) genes encoding molecular chaperones and ATP-dependent proteases, but it also increased and decreased expression of more than 300 genes related to disparate physiological functions. An extracytoplasmic-function sigma factor, SigH, was upregulated by heat shock. The SigH regulon was defined by gene expression profiling using sigH-disrupted and overexpressing strains in conjunction with mapping of transcription initiation sites. A total of 45 genes, including HSP genes and genes involved in oxidative stress response, were identified as the SigH regulon. Expression of some HSP genes was also upregulated by deletion of the transcriptional regulators HspR and HrcA. HspR represses expression of the clpB and dnaK operons, and HrcA represses expression of groESL1 and groEL2. SigH was shown to play an important role in regulation of heat shock response in concert with HspR and HrcA, but its role is likely restricted to only a part of the regulation of C. glutamicum heat shock response. Upregulation of 18 genes encoding transcriptional regulators by heat shock suggests a complex regulatory network of heat shock response in C. glutamicum.